Le regroupement des hôpitaux selon leur production : base d’évaluation de leur performance - Lance, Jean-Marie; Contandriopoulos, André-Pierre (L'Actualité économique, 1980)
Abstract The review of the budgetary bases of hospitals in Quebec is conducted in three stages: (1) classifying hospitals; (2) evaluating the performance of human and material resources used in each hospital as well as comparing this performance with the average performance of the peer-groups; (3) using the results to establish a correcting mechanism for an adequation redistribution of a portion of the total budget among individual hospitals. The realism of this process of budgetary review lies in the possibility of appropriately classifying the hospitals according to their output. In this paper, along with a short presentation, at the end, of the two last steps of the review process, we focus on the classification itself. We define firstly what constitutes the hospital's output, which is a mix of inpatient services (main variable), outpatient services, research and teaching, as well as environmental variables influencing the output. Then we describe the classification technique, which uses two different similarity indices, one for the distribution of patient-days by category of diagnosis (ICDA, 8th revision), and the other for all other variables; these indices are incorporated in a hierarchical sorting strategy based on the optimization of an objective function. This method is subsequently applied to the acute short-term hospitals of Quebec, using 1976-77 data, and the different resulting eight groups of hospitals are broadly described. In the conclusion, are indicated some suggestions for improving the classification and the budget reviewing mechanism itself.